2012
DOI: 10.5601/jelem.2010.15.3.425-433
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic values of calcium and magnesium forms determined in human serum and saliva

Abstract: Calcium and magnesium are known to be necessary for the normal function of various systems in animal and human organisms. There are many diseases caused by abnormal concentration of electrolytes, e.g. arterial hypertension or nervous system diseases such as multiple sclerosis, Mb. Alzheimer or Mb. Parkinson. The mechanisms of homeostasis indicate only the ionized forms of these elements. It is known that ionized calcium serves as an endocellular intermediary in action of enzymes and hormones in cells. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…Our study has shown that the levels of Ca 2+ , P and Mg 2+ are not changed, which is typical of the initial phase of osteoporosis, during which no signi cant loss of bone mineral density due to active bone remodeling and a compensatory increased osteoblast activity is seen [22,23]. Weight gain in animals in the G2 proves that lack of estrogens due to OVX leads to obesity [24,25].…”
Section: Discussionsupporting
confidence: 52%
“…Our study has shown that the levels of Ca 2+ , P and Mg 2+ are not changed, which is typical of the initial phase of osteoporosis, during which no signi cant loss of bone mineral density due to active bone remodeling and a compensatory increased osteoblast activity is seen [22,23]. Weight gain in animals in the G2 proves that lack of estrogens due to OVX leads to obesity [24,25].…”
Section: Discussionsupporting
confidence: 52%
“…The poor binding stability of conventional aptamer probes in biofluid is still a critical obstacle to their in vivo application. One important cause is the low level of Mg 2+ in biofluid, which acts as a chaperone in conformational folding of aptamers 29 , 30 . We thereupon investigated the binding property of NTri-SAAP in several representative buffers, including binding buffer, PBS with Mg 2+ supplied (+Mg), and PBS without Mg 2+ supplied (-Mg).…”
Section: Resultsmentioning
confidence: 99%
“…It is involved at multiple levels in insulin secretion, binding, and activity. [11] In our study serum, magnesium levels were similar in control group and Group A whereas it was decreased in Groups B and C. Andrusishina [12] (2010) has evaluated the serum and salivary magnesium levels with calcium levels in diabetic patients. They have observed that the levels of salivary and serum magnesium were nearly equal in normal subjects (n = 12), whereas it was decreased in the experimental groups (n = 27).…”
Section: Discussionmentioning
confidence: 99%